KOMPOSISI VEGETASI HABITAT BABIRUSA (Babyrousa babyrussa) DI KAWASAN HUTAN PENDIDIKAN UNIVERSITAS TADULAKO KECAMATAN BOLANO LAMBUNU KABUPATEN PARIGI MOUTONG - Anwarhadi, I Nyoman; Labiro, Elhayat; Korja, I Nengah (Jurnal Warta Rimba)
Tadulako University's Education Forest is one of Sulawesi's endemic wildlife habitats, namely Babyrousa babyrussa. The babirusa population is decreasing due to illegal hunting and illegal mining that destroys wildlife habitat. So it is necessary to conduct research on the composition of the Babirusa habitat vegetation. The study aimed to determine the composition of the Babirusa habitat vegetation in the Educational Forest Zone. Using a method of analysis of double plot vegetation which is placed by Purposive sampling as many as 3 square-shaped observation plots measuring 40 m x 40 m in the spot where the traces of babirusa are found. Each plot is made of 4 sub-plots measuring 20 m x 20 m for tree level, 10 m x 10 m pile level, 5 m x 5 m sapling level and 2 m x 2 seedling level. The results of the study found 29 types in 27 families of which 13 species in 12 families including Babirusa feed. 5 types of plants that comprise vegetation that are always found at the study site, besides the types of Dillenia sp., Are food sources of Babirusa (Babyrousa babyrussa): Pangium edule, Palaqum obtusilfolium Bulq, Lithocarpus elegans (Blume) Hatus. Ex Soepadmo, Calamus sp. The Index of Similarity in 3 study locations, at all vegetation levels ranged from 60.30% - 84.07% or> 75%. So that the composition of the vegetation of the three locations is considered almost the same.Keywords: composition of vegetation, babirusa habitat, forest education